Mesophotic Ecklonia radiata (Laminariales) at Rangitāhua, Kermadec Islands, New Zealand. Issue 5 (1st September 2018) - Nelson, Wendy; Duffy, Clinton; Trnski, Thomas; Stewart, Rob
Abstract: A population of the kelp Ecklonia radiata (Laminariales) has been found in mesophotic conditions at c . 72–80-m depth on the shelf surrounding Macauley Island, Rangitāhua, Kermadec Islands (30°13.3′S, 178°23.8′W), in northern New Zealand, c . 900 km northeast of New Zealand on the western margin of the South Pacific Subtropical Gyre. This species was identified morphologically and with sequence data. This is the first confirmed report of this kelp species growing at the Kermadec Islands, in a location four degrees farther north than previously recorded in the New Zealand archipelago. This discovery joins recent global reports of populations of Laminariales in deep tropical and subtropical habitats, postulated to serve as refugia and potential hot spots of diversity and productivity.